Values, motivational orientation and team cohesion amongst youth soccer players - Berengüí, R.; Carralero, R.; Castejón, M. A.; Campos-Salinas, J. A.; Cantón, E. (International Journal of Sports Science & Coaching, 2022)
There is a close link between moral education and sports activities. A well-organized sport can be an excellent means of transferring positive values to children and adolescents, which can influence motivation and group processes. This study aimed to analyse (a) the relationships between social, personal and individualistic values, motivational orientation and team cohesion amongst young soccer players and (b) compare differences in these variables between players competing in different age categories. Our participant sample comprised 401 male soccer players of Spanish teams (mean age = 14.64 years) competing in official competitive leagues, of five age categories, Under-10 years to Under-19. All participants responded to three instruments: the Values Scale for Positive Adolescent Development, the Perception of Success Questionnaire and the Group Environment Questionnaire. Correlation and regression, and analysis of differences between categories were performed. The results confirm that personal values are mainly related to task orientation, and individualistic values to ego orientation. The values of responsibility, integrity and honesty were the best predictors of task orientation, and social recognition and hedonism predict ego orientation. Honesty and responsibility were the main predictors of both task and social cohesion. Younger players showed a higher level of social values, task orientation and social cohesion, while older players show higher individualistic values and ego orientation. Implications for research or practice are discussed.